Development and validation of a questionnaire to assess health-related quality-of-life in cats with hyperthyroidism - Blunschi, Fabienne; Schofield, Imogen; Muthmann, Sofie; Bauer, Natali B.; Hazuchova, Katarina; Justus Liebig University Giessen (My University, 2024)
Background: Health-related quality-of-life (HRQoL) assessment tools are becoming increasingly important for the assessment of diseases in veterinary medicine. Objectives: To develop a tool to assess the HRQoL of hyperthyroid cats and their owners. Animals: Cats with hyperthyroidism (n = 229) and without hyperthyroidism (n = 322). Methods: Cross-sectional study design. A preliminary list of 28 questions relating to the HRQoL of hyperthyroid cats and the influence their cat's disease might have on owners was created. Each question consisted of 2 subquestions: (1) “how often does the item apply”; (2) “how strongly does the item affect HRQoL.” The questionnaire was refined based on statistical analysis, including Mann-Whitney-U tests on each item, comparing the results from cats with and without hyperthyroidism. Internal consistency and reliability of the questions were measured by Cronbach's alpha (α). P < .05 was considered significant. Results: Overall, 25/28 questions were retained within the final HRQoL tool, which had an excellent internal consistency (α = .92). The tool produced a score between 0 and 382 (lower scores meaning better HRQoL). The median HRQoL score was 87.5 (range, 2-348) for cats with hyperthyroidism, and 27 (range, 0-249) for cats without (P < .001), suggesting the HRQoL was poorer in hyperthyroid cats. Conclusions and Clinical Importance: This validated HRQoL tool is useful to reliably quantify the influence of hyperthyroidism on the quality-of-life of affected cats and their owners. In the future, it could be considered of assistance in the clinical assessment of cats with hyperthyroidism.
Keywords: ddc:630